Vascularized medial femoral condyle autografts for osteochondral lesions of the talus: a preliminary prospective randomized controlled trial - Struckmann, Victoria; Harhaus-Wähner, Leila; Simon, Rainer; Recum, Jan von; Wölfl, Christoph Georg; Kneser, Ulrich; Kremer, Thomas (The journal of foot and ankle surgery, 2020)
Talar osteochondral lesions (OCLs) lead to progressive stages of talar destruction. Core decompression with cancellous bone grafting (CBG) is a common treatment for Berndt and Harty stages II and III. However, in a subset of patients, talar revascularization may fail. Surgical angiogenesis using vascularized medial femoral condyle (MFC) autografts may improve on these outcomes. These 2 treatment strategies were directly compared via a prospective preliminary randomized trial including 20 participants with talar core decompression followed by either cancellous (CBG group, n=10) or vascularized MFC (MFC group, n=10) bone grafting. Outcome analysis was performed with visual analog scale (VAS), American Orthopaedic Foot and Ankle Society (AOFAS) ankle-hindfoot score, Lower Extremity Functional Scale (LEFS), and contrast-enhanced magnetic resonance imaging (MRI) scans. At 12 months of follow-up, the mean VAS score was reduced from 6.6 ± 2.5 preoperatively to 4 ± 1.9 in the CBG group and from 5.2 ± 2.9 preoperatively to 1 ± 1.1 in the MFC group (p < .001). The LEFS improved from 53.4 ± 13.1 to 62.6 ± 16.2 CBG and from 53 ± 9.3 to 72.4 ± 7.4 MFC (p=.114). AOFAS improved from 71 ± 12.1 to 84.1 ± 12.5 in CBG and from 70.5 ± 7.4 to 95.1 ± 4.8 in MFC (p=.019). The MRI scans in the CBG group demonstrated 9 partial malperfusions and 1 hypervascularized bone graft, whereas the MFC group had 8 well-vascularized grafts incorporated into the talus and 1 partial malperfusion. Vascularized MFC autografts provide superior pain relief along with improvement of physical function in patients with talar OCL stage II and III compared with CBG. To confirm these promising results, further multicenter randomized controlled trials are required.
Gesehen am 30.03.2020